Transplantasi Organ Tubuh sebagai Pengganti Hukuman Qhisas dalam Hukum Islam (Studi Terhadap Delik Pelukaan Mata) - Amin Ramly (SASI, 2019)
This paper deals with the study of Islamic criminal law, which regulates the study of transplants as a substitute for Qhishas punishment, the main issue is to see how the qhisas process of ophthalmic offenses, eye transplantation techniques, and fiqh analysis of eye transplants as a substitute for qhisas punishment. To be able to analyze the problems above, this study uses a type of qualitative research with a normative approach based on the rules of Islamic law (Al-Quran, hadith, and ijtihad), and analyzed by the inductive method according to the Shari'a perspective on the concept of transplantation as qhisas punishment. The results showed that the qhisas for the eye opening offense based on the argument of Al-Maidah verse 45, where the eye must be punished with the eyes, both in terms of the method of wounding practiced must be balanced between the victim and the offender, while the diyat above the eye opening offense is 100 dinars. The eye organ transplant can be done medically by removing the cornea of the eye rather than the eyeball, because the eyeball cannot be transplanted, and the transplant is carried out from the donor to the recipient on all medical requirements by medical means. The analysis of jurisprudence to the concept of eye transplantation as a substitute for the qhishas penalty in sharia is not allowed, because it does not meet the principle of qhishas justice, namely the balance between uqubah with deeds, where the offender is charged with qhishas punishment (medical eye opening) and also charged with diyat punishment (ie costs transplant operations that will be borne by the perpetrator) whose amount can be more than diyat value.